Manajemen supervisi kepala sekolah dalam upaya peningkatan mutu kinerja guru di SMA Negeri 1 Yogyakarta - Agustinus Mardiyono; Supriyoko Supriyoko (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2016)
The aim of research is to know and discuss deeper about 1) the implementation of headmaster supervision include planning, organising, implementation, and controlling in increasing the quality of teachers performance at SMA N 1 Yogyakarta, 2) the substances that supervised by headmaster for teachers at SMA N 1 Yogyakarta, 3) the strategy in increasing the quality of teachers performance at SMA N 1 Yogyakarta, and 4) the obstacles, feedback and problem solving of headmaster supervision in increasing the quality of teachers performance at SMA N 1 Yogyakarta. The research is a descriptive by using the qualitative approach. The informants consist of the headmaster, vice headmaster, teachers, committees, students and parents student. The collecting data is through on observation, deep interview, and documentation. The data is analyzed by using reduction, display, and verification. The validity of data is obtained through credibility, transferability, dependability, and confirmability. The result of the research shows that 1) the management supervision of SMA N 1 Yogyakarta has been good. The headmaster has done supervision schedule, estimate planning, ordered a senior teacher to help supervising, controlling and workshop. 2) the substances that supervised are learning administration, implementation, and learning control, 3) the strategy in increasing teachers performance has done by increasing planning ability, implementation and evaluation learning., 4) the obstacles in management supervision are the schedule of supervision and the problem is solved by using consultation the headmaster, senior teacher who ordered to help to supervise and curriculum vice headmaster to get deal of the effectivity schedule supervision.